2014
DOI: 10.1136/neurintsurg-2013-010982
|View full text |Cite
|
Sign up to set email alerts
|

Practical techniques for reducing radiation exposure during cerebral angiography procedures

Abstract: Replacing femoral arterial access evaluations by DSA with fluoroscopy, utilizing lower pulse rates during fluoroscopy and roadmap guidance, and choosing variable frame rates for DSA are simple techniques that may be considered by operators in their clinical practices to lower radiation dose during cerebral angiography procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 9 publications
0
46
0
Order By: Relevance
“…Pearl et al [18] recently made propositions to implement further dose reduction strategies: some of them were already routinely applied at our center as described in the Materials and Methods section, but others, such as the real-time monitoring of radiation parameters with thresholds to better control radiation level during each procedure or the use of a lower default DSA framerate (2 vs. 4 fps currently), should also be considered and evaluated with respect to adequate image quality and patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pearl et al [18] recently made propositions to implement further dose reduction strategies: some of them were already routinely applied at our center as described in the Materials and Methods section, but others, such as the real-time monitoring of radiation parameters with thresholds to better control radiation level during each procedure or the use of a lower default DSA framerate (2 vs. 4 fps currently), should also be considered and evaluated with respect to adequate image quality and patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Both operators use in routine some of the dose reduction strategies described by Pearl and colleagues [18,19] , which comprises of the use of fluoroscopy instead of DSA for the femoral access evaluation, the use of a low fluoroscopy framerate (7.5 fps) and variable-framerate DSA, recording of the radiation data, and for follow-up studies the re-use of sequences from previous procedures to minimize the use of DSA for evaluation of the aortic arch. In case of high-flow lesions, a higher DSA framerate is selected.…”
Section: Methodsmentioning
confidence: 99%
“…Operators should also be conscious of limiting usage of lateral or oblique views which vary the skin area radiated (‘dose spreading’) 22 24. Digital subtraction images are much higher resolution than pulsed fluoroscopy images and should be used only when pulsed fluoroscopy images are inadequate 25. When either digital subtraction angiography or pulsed fluoroscopy is used, the operator can set as few images as are necessary for diagnosis 26.…”
Section: Discussionmentioning
confidence: 99%
“…Further work by the same group used a change in DSA technique combined with a real-time noise reduction algorithm and demonstrated a reduction in the patient entrance dose by 75% (table 5). 17 Using adult skull and abdominal/pelvic anthropomorphic phantom models, Pearl et al 18 showed that replacing femoral arterial access DSA evaluations with fluoroscopy, using lower pulse rates during fluoroscopy and roadmap guidance, and choosing a variable frame rate for DSA are simple techniques to lower radiation dose during cerebral angiography procedures. In our clinical study, using some of the radiation reduction techniques used by Pearl et al in the phantom model, we achieved a 55% radiation dose reduction similar to results obtained by Soderman et al ; however, our results were achieved without employing an image noise reduction algorithm.…”
Section: Discussionmentioning
confidence: 99%